Statistical Differences in Set Analysis in Badminton at the RIO 2016 Olympic Games - Torres-Luque, Gema; Fernández-García, Ángel Iván; Blanca-Torres, Juan Carlos; Kondric, Miran; Cabello-Manrique, David (Frontiers in Psychology, 2019)
The aim of the present study was to determine statistical differences in a set of badminton competition matches in five different modalities with regard to competition level (Group Phase versus Eliminatory Phase). Data from 453 sets (125 in men’s singles; 108 sets in women’s singles; 77 sets in men’s doubles; 73 in women’s doubles and 70 in mixed doubles) from the RIO 2016 Olympics Games were recorded and classified in two groups of variables to analyse variables related to match (5) and set (15). A descriptive analysis and univariate test (Mann Whitney U) for non-parametric data were conducted. The results show in men’s and women’s singles all the variables related to match were higher in the Elimination Phase than in the Group Phase (p<0.01). In Sets 1 and 3, the longest set duration, rally and average rally were found in the Elimination Phase than Group Stage (p<0.05). In women’s singles, these differences were also recorded in Set 2. For doubles, the results are more stable among groups. Men’s doubles had a longer duration of the match and set (set 1 and set 2) (p<0.01), and also scored highest for average rally strokes (set 1 and set 3) (p<0.05) and shuttles used in the Elimination Phase versus the Group Phase along the match (p<0.01). In women’s doubles, more shuttles were used in a match in the Elimination than in the Group Phase. Moreover, the same results are established for Set 2, including for average rally. Mixed doubles saw no match going to three sets. However, the greatest differences showed a longer rally and average rally being registered in the Elimination than in the Group Phase. In conclusion, the timing factors of the badminton singles and doubles games were different in the Elimination and Group Phases. This information may help players and coaches prepare and administer different types of workouts or, more specifically, competition schedules adapted to the characteristics of modern badminton.